Exploring Indonesian EFL Classroom Interactions in an Online Setting - Muhammad Rafi Abdusyukur; Dadang Sudana; Ahmad Bukhori Muslim (UNIB Press, 2022)
COVID-19 pandemic has brought a lot of changes in the education field – including the way teachers and students interact in the classroom. As a result, it is considered important for the Indonesian EFL teachers to explore and address this issue to make them familiar with the current pattern of interaction in the online classroom. With that knowledge, making the online teaching and learning effective is achievable. Even though a lot of studies have been conducted on similar topic, this study propose a different analysis by adapting the most prevalent framework in this topic – Flanders Interaction Analysis Categories System (FIACS) – into more focused categories for better understanding. This case study aimed at exploring the interaction in an online EFL classroom by utilizing FIACS as the main framework. The necessary data was collected through non-participant observation, with an English teacher and her seven grade students as the participants. The results of this study show that the online EFL classroom interaction was dominated by the teacher. It was caused by several reasons namely the passiveness of the students that led to more talking from the teacher and technological glitches. It caused the online meetings to be teacher-centered. As the teaching and learning medium changed, the pattern and characteristics of the interaction became unique. One of the notable uniqueness was the difficulty to oversee the online interactions between students.